LEVEL OF LEAD IN THE BLOOD AMONG FUEL STATION EMPLOYEES AND ITS RELATIONSHIP TO IMPAIRED LIVER AND KIDNEY FUNCTIONS IN DAMASCUS; SYRIA: OCCUPATIONAL EXPOSURE TO LEAD - Al-Mahbashi, Hassan; Asfoura, Samira; Obri, Saad; Al-Maqtari, Tareq; Abudunia, Abdulmalik (Universal Journal of Pharmaceutical Research, 2020)
Objectives: Chronic exposure to lead is known to cause adverse health effects. Workers at fuel stations are exposed to high concentrations of lead during filling cars and through Car’s emissions and being in contact with contaminated hands, food, water and clothing. This study was designed to find blood lead level and their adverse effects on kidney and liver function among fuel station workers. Methods: Forty fuel station workers (exposed group) and thirty apparently healthy subjects (non-exposed group) in Damascus were randomly selected for the study. Blood lead levels were determined using Atomic absorption spectrometry after microwave-assisted acid digestion. Serum concentration of creatinine, uric acid and urea values were recorded to assess kidney function, whereas AST and ALT serum concentrations were used to evaluate liver function. Results: The results showed a non-significant elevation of blood lead level in the exposed group (11.04 ± 10.36 µg/dl) compared to the non- exposed group (8.1±2.97 µg/dl). Serum concentration of creatinine and uric acid were significantly elevated in the exposed group, but there was no change in AST and ALT serum levels. Conclusion: It is concluded that blood lead levels of fuel station workers don’t exceed the threshold that may cause kidney or liver dysfunctions. Peer Review History: Received 1 February 2020; Revised 10 March; Accepted 25 April; Available online 15 May 2020 Academic Editor: Dr. Amany Mohamed Alboghdadly , Princess Nourah bint abdulrahman university, Riyadh, amalbgadley@pnu.edu.sa Reviewer(s) detail: Dr. Ali Abdullah Al-yahawi , Al-Razi university, Department of Pharmacy, Yemen, alyahawipharm@yahoo.com Prof. Dr. Hassan A.H. Al-Shamahy , Sana’a University, Yemen, shmahe@yemen.net.ye Dr. Asia Selman Abdullah , Al-Razi university, Department of Pharmacy, Yemen, asia_abdullah65@yahoo.com